4CPS-216 Role of the hospital pharmacist in the management of drugs not adapted to patients with dysphagia. (2nd March 2018) - Rossignoli, A; Molina, M; Andrés, S de; Jiménez, C; Alvarez, J; Sobrino, C; Moreno, M; Herrero, A
Abstract : Background: Dysphagia is usually caused by stroke, dementia, ageing or progressive conditions. Manipulations of solid drugs occur frequently in these patients, which may alter bioavailability, efficacy and/or side-effect profile of drugs, leading to medicine administration errors (MAEs). Purpose: The aim of this study was to analyse the drugs most frequently prescribed requiring manipulation in patients with swallowing difficulties, and of these, those which are not suitable for use in this manner (enteric coats, small therapeutic windows, slow release, etc.). Material and methods: A prospective longitudinal study was performed (2 months) in the internal medical unit. Pharmacotherapy prescribed to inpatients with dysphagia was evaluated using a CPOE program. Data collected were: age, drugs requiring manipulation and if manipulation was possible. To avoid MAEs, the pharmacist performed interventions to the nurse and/or prescriber. Acceptance or rejection of the intervention was measured. Results: Pharmacotherapy of 54 inpatients was analysed. Median age was 82 years. Each patient received (on average) 12 different drugs. Seventy-seven per cent of oral drugs were not in an appropriate dosage form. The pharmacist performed a total of 82 interventions: 48 of them involved drugs that could be crushed/dispersed but had alternatives that the physician could switch (liquid or dispersible oral forms) or required precautions associated with manipulation by the nurse (vehicle more appropriate to disperse, worker protection). All interventions were accepted. Drugs most frequently involved were: acenocoumarol with five interventions; levodopa/carbidopa with four; enalapril, pregabalin, risperidone and digoxin with three; and omeprazole, silodosin, amlodipine, duloxetine and atenolol with two. The pharmacist detected 22 different MAEs and performed 34 interventions to avoid them: 15 to the physician (involving drugs not suitable for manipulation), recommended switching to an alternative (67% interventions accepted) and 19 to nurses due to incorrect manipulation (37% accepted). Drugs involved were: pantoprazole with eight interventions, acetylsalicylic-acid and dutasteride/tamsulosin with three, spironolactone with two and other drugs with one. Conclusion: Most of the oral medications prescribed to patients with dysphagia were manipulated, which can promote MAEs. The increased MAE rate in these patients means that health professionals need to take extra care when prescribing and administering drugs to these patients. Hospital pharmacists should assess the suitability of medication formulations and discuss swallowing difficulties with the prescriber. References and/or Acknowledgements: Acknowledgements to pharmacists and internal medical unit No conflict of interest